A systematic review and meta-analysis of neopterin in rheumatic diseases - Mangoni, Arduino A.; Zinellu, Angelo (Frontiers in Immunology, 2023)
Novel biomarkers of inflammation and oxidative stress might enhance the early recognition, management, and clinical outcomes of patients with rheumatic diseases (RDs). We assessed the available evidence regarding the pathophysiological role of neopterin, the oxidation product of 7,8dihydroneopterin, a pteridine generated in macrophages activated by interferon-g, by conducting a systematic review and meta-analysis of studies reporting its concentrations in biological fluids in RD patients and healthy controls. We searched electronic databases for relevant articles published between inception and 31 August 2023. The risk of bias and the certainty of evidence were assessed using the Joanna Briggs Institute Critical Appraisal Checklist and the Grades of Recommendation, Assessment, Development and Evaluation Working Group system, respectively. In 37 studies, when compared to healthy controls, RD patients had significantly higher concentrations of neopterin both in plasma or serum (standard mean difference, SMD=1.31, 95% CI 1.01 to 1.61; p˂0.001; moderate certainty of evidence) and in the urine (SMD=1.65, 95% CI 0.86 to 2.43, p˂0.001; I 2 =94.2%, p<0.001; low certainty of evidence). The results were stable in sensitivity analysis. There were nonsignificant associations in meta-regression and subgroup analysis between the effect size and age, male to female ratio, year of publication, sample size, RD duration, C-reactive protein, erythrocyte sedimentation rate, specific type of RD, presence of connective tissue disease, analytical method used, or biological matrix investigated (plasma vs. serum). By contrast, the effect size was significantly associated with the geographical area in studies assessing serum or plasma and with the type of RD in studies assessing urine. Pending additional studies that also focus on early forms of disease, our systematic review and meta-analysis supports the proposition that neopterin, a biomarker of inflammation and oxidative stress, can be useful for the identification of RDs. (PROSPERO registration number: CRD42023450209).